Defining the Concept of Competence: a Systematic Literature Review - Tarekegne, Chalachew (Ethiopian Journal of Social Sciences, 2018)
Performance in the actual job environment is a much more investigated area. In the field of psychology, human resources development and education, the concept of competence is a prerequisite for and the centre of analysis. This article review focuses on how competence is conceptualized in the literature during 1950-2010. A systematic review was done using the google scholar search engine which covers different fields of social sciences like psychology, human resources development, and education, among others. The search was operated by using the word ‘competence’ and the phrase ‘competence-based education’. Six articles that were written in English and published between 1950-2010 were identified. However, after judging their relevance, two articles were excluded because of duplication and focus on competence for firm competitiveness instead of defining it. Hence, four articles were included and submitted for data extraction. The selected articles were assessed for biases based on three quality assessment criteria enlisted as: methodological quality, precision, and external validity. Following the quality assessment for biases, data were analysed qualitatively using content analysis method. Thematic synthesis was used to bring the findings from those 4 articles together. Though there are different theoretical assumptions related to it, it is concluded, competence is conceptualized as the acquisition of knowledge, skills, and attitudes by the learners/trainees to achieve superior performance in the actual job environment.